The impact of sulfonylureas on diverse ion channels: an alternative explanation for the antidiabetic actions - Xian-Tao Li; Meng-Ze Yun (Frontiers in Cell and Developmental Biology)
The oral hypoglycemic drug sulfonylureas exhibit substantial therapeutic benefits for millions of patients with type 2 diabetes mellitus (T2DM), although with common adverse effects, such as hypoglycemia. It is generally believed that inhibition of KATP channels by sulfonylureas in pancreatic β-cells enables the insulin release to reduce glycemic levels, a primary mechanism underlying pharmacological effectiveness. Accumulated evidence reveals that multiple ion channels, such as Kv and TRP, are also expressed in β-cells in the pancreatic islets of Langerhans, and these channels, particularly Kv2.1, show important functional roles in tuning the electrical activity of β-cells, accordingly participating in the modulation of insulin secretion. Existing data reveal that several ion channels besides KATP channels could be directly blocked by sulfonylureas, and consequent membrane depolarization serves to facilitate the insulin release, possibly contributing to glycemic control or side effects. Furthermore, the modulation of sulfonylurea-mediated activation of Epac2A on diverse ion channels could produce the pharmacological efficacy, indicative of an indirect regulatory way. The scenario of sulfonylureas impacting diverse ion channels may provide an alternative explanation for the antidiabetic actions and side effects, extending our understanding of these classical clinic drugs.